2020
DOI: 10.3390/md18060288
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Peptides from the Oyster (Crassostrea hongkongensis) Protein Hydrolysates against UVB-Induced Skin Photodamage in Mice

Abstract: Chronic exposure to ultraviolet B (UVB) irradiation is a major cause for skin photoaging. UVB induces damage to skin mainly by oxidative stress, inflammation, and collagen degradation. This paper investigated the photo-protective effects of peptides from oyster (Crassostrea hongkongensis) protein hydrolysates (OPs) by topical application on the skin of UVB-irradiated mice. Results from mass spectrometry showed that OPs consisted of peptides with a molecular weight range of 302.17–2936.43 Da. In vivo study demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 51 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…The amino acid of the SNCP was determined according to the previous study [ 56 ]. SNCP was hydrolyzed by dissolving it in 6 M HCl at 110 °C for 24 h. The filtrate and standard samples of amino acids solution was analyzed with an automatic amino acid analyzer (S-433D, Sykam, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid of the SNCP was determined according to the previous study [ 56 ]. SNCP was hydrolyzed by dissolving it in 6 M HCl at 110 °C for 24 h. The filtrate and standard samples of amino acids solution was analyzed with an automatic amino acid analyzer (S-433D, Sykam, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…OPs were prepared by enzymatic hydrolysis from the oyster meat according to the methods of Li et al, Peng et al, and Zhang et al [ 17 , 41 , 47 ]. Briefly, three kilograms of oyster meat were ground into mince and then mixed with distilled water (1:3 w / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Sodium citrate buffer solution was added to the dried test tube and dissolved. The solution was transferred to the injection flask of the instrument for determination by the amino acid analyzer [ 47 ]. According to the peak area in comparison with the standard, amino acid contents were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Kaul et al in vitro evidence suggests that L-proline acts as a radical scavenger [ 60 ]. There is evidence that cysteine may act as a radical scavenger as well [ 44 , 51 , 61 , 62 ], and cysteine has been implicated as an AA residue abundant in numerous anti-inflammatory BAPs [ 48 ]. One potential mechanism of cysteine’s anti-inflammatory activity is IL-15Rα binding and agonism [ 29 ].…”
Section: Fish and Shellfish-derived Anti-inflammatory Protein Products: Properties And Mechanismsmentioning
confidence: 99%
“…One potential mechanism of cysteine’s anti-inflammatory activity is IL-15Rα binding and agonism [ 29 ]. A study by Peng et al [ 62 ] found that hydrolysates high in radical scavenging peptides including cysteine, methionine, and tryptophan ameliorated the effects of UVB radiation in mice models by increasing enzyme activity of superoxide dismutase (SOD), and glutathione peroxidase (Gpx), while decreasing levels of malondialdehyde, IL-1β, IL-6, TNF-α, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) in mice models when applied topically.…”
Section: Fish and Shellfish-derived Anti-inflammatory Protein Products: Properties And Mechanismsmentioning
confidence: 99%